Study of the antibacterial activity of thymol and carvacrol monoterpenes against strains of Escherichia coli producing extended-spectrum β-lactamases - Lima, Dijaci Santos de (2019)
OBJECTIVES: To study the antimicrobial activity of thymol and carvacrol phytochemicals against strains of Escherichia coliproducing extended-spectrum β-lactamases (ESBL) and to determine the minimum inhibitory concentration (MIC) of thymol and carvacrol. MATERIALS AND METHODS: The experiments were carried out at the Microbiology Laboratory (J11) at the Education and Health Center of the Universidade Federal de Campina Grande, Paraíba State, Brazil. In order to determine the MIC of the selected phytocompounds, bacterial strains of E. coli ESBL (C-18, C-21, C-20, C-24, C-25, 24, 65) from outpatients were used, and microdilution technique in 96-hole reaction plate by two-fold serial dilution, reserving the last column for growth control of microorganisms. RESULTS: MIC of carvacrol showed concentrations of 64 μg/mL for strain 65 and 128 μg/mL for strains C-18, C-20, C-21, C-24, C-25, and 24. In the thymol action, MIC was determined as: 1,024 μg/mL for strain C-25; 512 μg/mL for C-18, C-21, 24, and 65; 256 μg/mL for C-24; and 128 μg/mL for strain C-20. CONCLUSION: Through the experiments it was possible to affirm that the phytocompounds carvacrol and thymol have bacteriostatic effects on E. coli strains.